The bioeconomy as a business model in Ecuador (Revista Científica Compendium, 2021)
The bioeconomy is an emerging model that proposes the use of available biomass in order to transform it into a variety of products that traditionally comes from non-renewable resources. As compared with Latin America, the European countries have a greater advantage in terms of experiences related to the adoption of bioeconomy policies. Ecuador is characterized by having a primary economy, but it has the potential to migrate in the medium or long term, to a biologically based productive matrix. The following is a very concise presentation of the country's progress in terms of the bioeconomy. Based on a bibliographic search in regional and international scientific publications, the strategies of some countries in the matter are analyzed and the steps taken by Ecuador are exposed. Finally, some strategies for the implementation of a bioeconomic model in the country are presented. Although it represents a challenge, its materialization would give way to new opportunities for the Nation.
Keywords: circular economy; bioeconomic model; Latin America